Biopsychosocial determinants of visuospatial memory performance according to different spaces. (September 2021) - Gallou-Guyot, M.; Mandigout, S.; Lacroix, J.; Ricard, D.; Buffat, S.; Archambeau, D.; Guéguin, G.; Perrochon, A.
Highlights: Biopsychosocial determinants of VSM performance in pathway learning differ according to space Mental rotation and fatigue are associate with VSM performance in reaching space Mental rotation and physical activity are associate with VSM performance in walking space Abstract: Visuospatial memory (VSM) performance depends on intrinsic (biopsychosocial parameters) and extrinsic (space) factors. We aimed at characterizing the determinants of VSM performance according to space. Young healthy adults, 20 males and 41 females (23 ± 3 years old), were assessed for VSM performance through a pathway learning task, in reaching (eCorsi Block Tapping task) and walking space (Virtual Walking Corsi Task). We evaluated psychosocial factors through seven questionnaires – Epworth Sleepiness Scale, Pittsburgh Sleep Quality Index, Fatigue Severity Scale, Profile of the Mood States, 2 nd edition, short version, Coping Inventory for Stressful Situations, Measurement of Ambiguity Tolerance, Motives for Physical Activities Measure-Revised, mental rotation capabilities and locomotor characteristics (physical activity level through embedded trackers and the International Physical Activity Questionnaire, and gait parameters). The most explanatory biopsychosocial determinants of VSM performance were i) mental rotation capabilities and fatigue indicator in reaching space, and ii) mental rotation capabilities and physical activity level (tracked active energy expenditure only) in walking space. These results suggest that specific parameters should be preferred for the evaluation and strengthening of VSM capabilities in both reaching or walking spaces.